2015
DOI: 10.5455/bcp.20141212113905
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Plasma Levels of Prolactin and the Severity of Negative Symptoms in Patients with Schizophrenia

Abstract: Relationship between plasma levels of prolactin and the severity of negative symptoms in patients with schizophrenia Objective: The aim of this study was to evaluate the relationship between plasma levels of prolactin and negative symptoms. Methods: One hundred fourteen patients with schizophrenia were included in this crosssectional study. The patients were classified into groups with and without hyperprolactinemia. Plasma levels of prolactin and clinical features were compared between these groups. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
(80 reference statements)
1
3
0
Order By: Relevance
“…Although other studies have found that prolactin levels are inconsistently associated with efficacy (Wang et al, 2007;Lostia et al, 2009), our study revealed that prolactin levels may induce changes in neurogenesis, potentially affecting aberrant behaviors in ASD, consistent with several other studies (Zhang et al, 2002;Lee and Kim, 2006;Ates et al, 2015). Prolactin is an anterior pituitary peptide hormone, under inhibitory control by dopamine released from the tuberoinfundibular dopaminergic neurons (Grattan, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although other studies have found that prolactin levels are inconsistently associated with efficacy (Wang et al, 2007;Lostia et al, 2009), our study revealed that prolactin levels may induce changes in neurogenesis, potentially affecting aberrant behaviors in ASD, consistent with several other studies (Zhang et al, 2002;Lee and Kim, 2006;Ates et al, 2015). Prolactin is an anterior pituitary peptide hormone, under inhibitory control by dopamine released from the tuberoinfundibular dopaminergic neurons (Grattan, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Zhang et al (2002) observed a significant positive relationship between the reduction rate of positive subscale scores of the Positive and Negative Syndrome Scale (PANSS) and the change in prolactin levels before and after treatment in chronic schizophrenia. Ates et al (2015) found that in patients with hyperprolactinemia, the PANSS negative symptom scores were significantly higher than in patients without hyperprolactinemia (p 0.041). Furthermore, several moderators and mediators affecting risperidone response have been described (Stern et al, 2018), and lower baseline levels of prolactin predict responder status in autistic children.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Hyperprolactinaemia has been observed among patients on antipsychotic medications with greater D2 receptor binding, especially those on typical antipsychotics. 5 , 6 In most cases, the atypical antipsychotics have a lower propensity to increase prolactin levels than typical antipsychotics with clozapine, olanzapine and quetiapine only mildly and transiently elevating prolactin levels while risperidone and amisulpride with greater affinity to D2 receptors causing a marked and sustained increase in serum prolactin levels. 7 , 8 In addition, the tendency of antipsychotics to elevate plasma prolactin level is dose dependent with higher doses more likely to result in high prolactin levels.…”
Section: Introductionmentioning
confidence: 99%